EP.FRI.35 Traumatic abdominal wall hernia (TAWH) in a 16 year old boy. (28th October 2021) - Ahmed, Elmurtada; Shaw, Simon
Abstract: Definition: Traumatic abdominal wall hernia is defined as: herniation of viscera through disrupted musculature & fascia associated with forceful trauma without skin penetration & no evidence of prior hernia defect prior to trauma Introduction: There are only about 30 reported cases of TAWH due to handlebar injury, it is a rare complication of blunt abdominal trauma it involves disruption of abdominal wall muscles with bowel loops herniating through the abdominal wall defect & may be accompanied by serious or lethal complications Case report: A 16 year old boy received trauma while cycling at about: 5 miles/hour & landed in the handle-bar with his right lower abdominal wall against the handle, the patient's vital signs were stable but there was bruising in the area, the diagnosis was missed by A&E doctor, but I saw him O/E there was a positive cough impulse & the diagnosis was confirmed by US examination, his haematological & biochemical investigations were normal, patient was taken to theatre & the hernia was repaired (image 2 & 3) Conclusion: our case highlights the importance of clinical examination in blunt abdominal trauma & high index of suspicion plus using US/CT as appropriate to rule out mesenteric or visceral injury